2003
DOI: 10.1002/art.10902
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dynamic strength training on physical function, Valpar 9 work sample test, and working capacity in patients with recent‐onset rheumatoid arthritis

Abstract: Objective. To study the impact of 24 months of strength training on the physical function of patients with early rheumatoid arthritis (RA). Methods. Seventy patients were assigned to either the strength training (experimental) group (n ‫؍‬ 35) or the control group (n ‫؍‬ 35). Patients in the experimental group performed strength training for 24 months, and control patients were instructed to perform range of motion exercises. Maximal strength of the knee extensors, trunk flexors, and extensors, as well as grip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 26 publications
2
23
0
3
Order By: Relevance
“…We also found, similar to other published studies, that many individuals with RA have very low levels of physical activity (10,11) in spite of the demonstrated safety of exercise and published guidelines recommending physical activity for persons with RA (12). Although studies have examined the impact of exercise interventions on RA outcomes, most have focused on pain or function (13)(14)(15)(16)(17). Two recent systematic reviews found that physical activity did have beneficial effects on fatigue (18,19), but most exercise interventions have been resource intensive, requiring specially trained personnel, highly structured activities, and/or attendance at classes or a specified facility.…”
Section: Introductionsupporting
confidence: 88%
“…We also found, similar to other published studies, that many individuals with RA have very low levels of physical activity (10,11) in spite of the demonstrated safety of exercise and published guidelines recommending physical activity for persons with RA (12). Although studies have examined the impact of exercise interventions on RA outcomes, most have focused on pain or function (13)(14)(15)(16)(17). Two recent systematic reviews found that physical activity did have beneficial effects on fatigue (18,19), but most exercise interventions have been resource intensive, requiring specially trained personnel, highly structured activities, and/or attendance at classes or a specified facility.…”
Section: Introductionsupporting
confidence: 88%
“…Several studies have reported that grip force increases as a result of interventions (30,(37)(38)(39)(40)(41)(42). The results in the present study also indicate that increasing the grip force may result in reduced activity limitations.…”
supporting
confidence: 79%
“…11 Improvements in aerobic capacity were reported by a number of the aerobic and combined exercise programmes 12-14, 20, 25 , but not by the pure strength training programmes. [16][17][18][19]25 Conversely the strength training programmes report significant increases in muscle strength but not in aerobic capacity.…”
Section: Discussionmentioning
confidence: 99%
“…The studies by Hakkinen et al 15,16,17,18,19 years. 23 The intervention was concentric quadriceps and hamstring training.…”
Section: Strength Trainingmentioning
confidence: 99%
See 1 more Smart Citation